PROSES KOMUNIKASI KONSELOR DENGAN KLEIN NARKOBA KASI PASCAREHABILITASI BADAN NARKOTIKA NASIONAL PROVINSI SULAWESI TENGAH - Rais, Dewi Oktavianty (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
The aim of the research is to determine the interpersonal communication process between counselors and clients at the National Narcotics Agency of Central Sulawesi Province, post-rehabilitation section. This type of research is descriptive qualitative with research location. Central Sulawesi Province National Narcotics Agency. In this study, ten people were selected using sampling techniques. Data collection techniques were carried out using in-depth observation. Data analysis techniques use data analysis and qualitative. The results of research related to interpersonal communication between counselors and clients show that the communication process begins with the desire of the communicator, in this case the counselor, to facilitate the client in counseling guidance, the counselor's desire to communicate using words and sentences verbally or in writing so that it can influence the client, the counselor can creating a comfortable atmosphere in counseling guidance, to encode the counselor can formulate the contents of his mind to find out how to communicate by asking questions that do not make the drug client relapse, then the counselor sends messages via counseling guidance to drug clients face to face and monitoring via telephone. After that, the drug client receives a message from the counselor through counseling guidance. The counselor who sends a message via a question will decode this so that it can be understood by the drug client, for the initial goal, namely to return the client to his social function and maintain recovery. Then the drug client will understand the message of the question and will respond or provide a response from the drug client, so that the client will open up and accept the advice and input given by the counselor.